1989
DOI: 10.1152/ajprenal.1989.257.5.f842
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane calcium pump and 28-kDa calcium binding protein in cells of rat kidney distal tubules

Abstract: In an effort to extend our studies on Ca2+ pumps to animal models, we developed a new monoclonal antibody (5F10) prepared against the human erythrocyte Ca2+-Mg2+-adenosinetriphosphatase (ATPase) that recognizes a protein of approximately 140 kDa in rat kidney homogenates. Enzyme-linked immunosorbent assays show that monoclonal antibody 5F10 binds purified Ca2+-Mg2+-ATPase and rat kidney membrane extracts in a concentration-dependent manner. In paraffin-embedded tissue sections, antibody 5F10 binds to an epitop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 0 publications
9
75
0
Order By: Relevance
“…Expression of PMCA The monoclonal anti-PMCA antibody detected a broad protein band at around 140 kDa (∼133-147 kDa) and a smaller band at 92 kDa, consistent with previous observations [19]; these bands were absent from negative control blots (data not shown). The relative density of the major immunoreactive species at ∼140 kDa, representing PMCA [19], was significantly greater in the OD rats than in the OC rats, in both neonatal (Fig.…”
Section: Western Blottingsupporting
confidence: 91%
See 2 more Smart Citations
“…Expression of PMCA The monoclonal anti-PMCA antibody detected a broad protein band at around 140 kDa (∼133-147 kDa) and a smaller band at 92 kDa, consistent with previous observations [19]; these bands were absent from negative control blots (data not shown). The relative density of the major immunoreactive species at ∼140 kDa, representing PMCA [19], was significantly greater in the OD rats than in the OC rats, in both neonatal (Fig.…”
Section: Western Blottingsupporting
confidence: 91%
“…The relative density of the major immunoreactive species at ∼140 kDa, representing PMCA [19], was significantly greater in the OD rats than in the OC rats, in both neonatal (Fig. 2a) and adult ( Fig.…”
Section: Western Blottingmentioning
confidence: 93%
See 1 more Smart Citation
“…We observed similar motor terminal staining when using a monoclonal antibody prepared against the human erythrocyte PMCA (Borke et al, 1989). This staining pattern indicates that the PMCA protein is concentrated in the presynaptic terminals; however, we cannot rule out that PMCA concentrated in the postsynaptic membrane contributes to the observed staining pattern.…”
Section: Anti-pmca Western Blots and Immunocytochemistrymentioning
confidence: 51%
“…Kim et al (10) demonstrated that both PMCA1b and PMCA4b bind to PDZ domains, although PMCA4b was observed to have significantly higher affinity. To determine the relative distribution of the two isoforms in the cytoskeleton, monoclonal antibodies 5F10 and JA9 were employed (22,23); 5F10 recognizes both isoforms, whereas JA9 only binds PMCA4. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%